DIC TEXTURING-ASSISTED ACCELERATED SOLVENT EXTRACTION OF ACTIVE MOLECULES OF POMEGRANATE PEEL (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The current work discusses the use of Instant Controlled Pressure Drop (DIC) as a pretreatment texturing stage intensifying phenolic compound extraction from South Tunisian Punicagranatum L. peels in both cases of conventional and Accelerated Solvent Extraction (ASE). Response Surface Methodology (RSM) allowed identifying the effects of DIC processing parameters on the yields of Total Phenol Compounds (TPC), Total Flavonoid (TF), Condensed Tannins (CT), and Hydrolysable Tannins (HT), and antioxidant capacities via 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging capacity and ÃŸ-carotene-linoleic acid as responses. Comparative methods were used to evaluate DIC-textured and Raw samples. The results obtained confirmed that appropriate DIC-texturing improved both kinetic and yield of bioactive compound extraction using ASE from Punicagranatum L. peels. Extraction kinetics was studied through Coupled Washing-Diffusion CWD model. The effective diffusivity was identified and quantified ranged from 0.27 to 8.22 against 0.4710-10 m2s-1 for DIC textured and raw material (RM), respectively. DIC swelling enabled solid vegetal material matrix to expand and be more adapted to mass transfer thus increasing extractability of the phenol compounds. Scanning Electron Microscope SEM showed that DIC generated pores with an average diameter of 50 Âµm.